Penggunaan Biofungisida Pelet Trichoderma harzianum pada Pembibitan Awal Kelapa Sawit - Elfina S, Yetti; Ali, Muhammad; Delfina, Delfina (Jurnal Agro Teknologi Tropika, 2015)
Ganoderma boninense Pat. is one of the pathogens that infects young, immature and mature palm oil plants. Theinfection of the fungus can cause the death of palm oil plants, causing a decrease in the production of the plants.Alternative control of the disease is biological control using granular biofungicide containing Trichoderma harzianum.One factor that determines the success of the biofungicide is the dosage used. This study aims to determine the effect ofvarious dosages of T. harzianum granular biofungicide to control G. boninense and to study its effect on the growth ofyoung palm oil plants at pre nursery stage and obtain the best dosage in controlling G. boninense and to increasegrowth of young palm oil plants. This study was performed experimentally using completely randomized design consistingof 5 treatments and 4 replications. Each replication consisted of 2 young palm oil plants in medium of 4 kg soil/polybag.The treatment is dosage of granular biofungicide T. harzianum: 0, 5, 10, 15 and 20 g/polybag. The data were analyzedstatistically using analysis of variance and the means of treatment were tested with Duncanâs New Multiple Range Test(DNMRT) at level 5%. The results showed that dosage of granular biofungicide was significantly affected to control theG. boninense and to increase the height of the young plants and the volume of root of the young plant in the pre nurserystage. Dosage of granular biofungicide 10 g/polybag gave a better control to G. boninense (lowest diseases intensity:15,63 %) and to increase growth of young of palm oil plants than other dosages.